Oxford international primary Science student book 4 - Roberts, Deborah (Karachi : Oxford university press, 2021)
The Oxford International Primary Science Student Book 4 (Second Edition) provides young learners with a deeper understanding of scientific concepts. It covers topics such as the human body, plants, materials, energy, and the environment. The book is designed to engage students through clear explanations, activities, and experiments that encourage exploration and inquiry. With review questions, vocabulary-building exercises, and hands-on tasks, it reinforces key scientific ideas while aligning with international curricula, ensuring a comprehensive and interactive learning experience.
Keywords: Science : Textbook; Oxford : second edition